Assessment of The Effect of the Rainfall Returns Period and Pattern on The Hillslope Erosion on The Catchments (Case study: Heshan Basin) - Amin Zorati Pour; Mahmoud Arab Khedri (علوم و مهندسی آبیاری, 2016)
Soil erosion is a complex phenomenon involving the detachment and transport of soil particles, storage and runoff of rainwater. The relative magnitude and importance of these processes depends on a host of factors, including climate, soil, topography, cropping and land management practices, control practices. The rainfall intensities and frequency are the effectible factors important on magnitude of the soil loss. The purpose of this research is the assessment of effect and contribution of the high intensity rainfalls (return period 100 years) rather than the low and medium intensity rainfalls (return period 2 and 20 years) on soil erosion rate and flow hydraulics parameters and also the awareness hypothesis that the high intensity rainfalls are more effective than the periodic numbers of low intensity rainfalls. The study carried out on Marl soil of degraded rangeland from Heshan sub-basin by using of the rainfall and erosion simulator laboratory. The results of 18 experiments rainfall-runoff test showed that changes in return periods of rainfall from 20 years to 100 years and from 2 years to 20 years, respectively, has growth 2 times and 6 times flow unit, that it lead up increases accelerated from 3.3 times and 16 times of the amount of the Marl soil loss. So the rainfalls with high return period have aggregation periodic impact less than of the rainfalls with the low return period. Also increases the return periods to higher rainfall intensity have the progressive, direct and nonlinear effect on the amount of soil loss is Marl lands. Also, the slope percent show exponentially impacts in progressive 3 to 6 times on the discharge flow and then on the soil loss. Finally, the slope gradient and rainfall intensity factors separately and interaction effects on soil loss have high significant at one percent level.